The impact of calcination on changes in the physical and mechanical properties of the diatomites of the Leszczawka Member (the Outer Carpathians, Poland) - Figarska-Warchoł, Beata; Rembiś, Marek; Stańczak, Grażyna (Geology, Geophysics and Environment, 2020)
The work concerned the effects of the thermal treatment of diatomites from the Jawornik deposit (an example of the diatomites of the Leszczawka Member of the Polish Outer Carpathians). Five distinct lithological varieties were subjected to calcination at 600°C in ambient air. The thermal impact induced the following changes to the rocks. Their overall rock porosity increased, most distinctly in the initially softer varieties, and the internal pores of the siliceous frustules themselves usually became larger due to the initial melting of the silica phases. Most of the diatoms, quartz and feldspars cracked as a result of their brittle fracturing under compressive strain resulting from substantial and differing size changes of growing grains. Clay minerals were thermally transferred, changing their volume. The organic matter dispersed throughout the diatomites was partly oxidized and removed. At the same time, the structure of the rocks was strengthened, as confirmed by an increase in their microhardness. The microhardness of soft and porous diatomite varieties increased considerably on heating, but that of the hard and compact variety changed to a smaller degree. The increase is directly related to the content of the clay minerals. The impact of other mineral components was not detected. The calcination of lithologically diversified diatomites provided the mineral with raw material with deicing and antisliding properties. The technology of its production has been determined by the authors and submitted as a patent.